Towards Braiding (Gesturing Towards Decolonial Futures, 2019)
Towards Braiding  is an on-going collaborative process between Elwood Jimmy and Vanessa Andreotti hosted and funded by the Musagetes Arts Foundation. This collaboration involves several modes of re…